Correction: Dehydrocoupling of phosphine–boranes using the [RhCp*Me(PMe3)(CH2Cl2)][BArF4] precatalyst: stoichiometric and catalytic studies. Issue 3 (9th February 2016) - Hooper, Thomas N.; Weller, Andrew S.; Beattie, Nicholas A.; Macgregor, Stuart A.
Abstract : Correction for 'Dehydrocoupling of phosphine–boranes using the [RhCp*Me(PMe3 )(CH2 Cl2 )][BAr F 4 ] precatalyst: stoichiometric and catalytic studies' by Thomas N. Hooper et al., Chem. Sci., 2016, DOI: 10.1039/c5sc04150c.